Anguilla bicolor McClelland 1844 ... - Esmaeili, Hamid Reza; Hamidan, Neshat (Zenodo, 2023)
2. Anguilla bicolor McClelland, 1844 ―Shortfin Eel― Native Taxonomy. Original description: Anguilla bicolor McClelland, 1844:178, 202, 209, Pl. 6 (fig. 1) [Sandoway, Malay coast, India; Syntypes: SMF 776 (1)]. Synonyms: Anguilla amblodon Günther, 1867; Anguilla bleekeri Kaup, 1856; Anguilla cantori Kaup, 1856; Anguilla dussumieri Kaup 1856; Anguilla foochowensis Chu & Jin, 1984; Muraena halmaherensis Bleeker, 1863; Muraena macrocephala Rapp, 1849; Anguilla malabarica Kaup, 1856; Anguilla malgumora Kaup, 1856; Anguilla moa Bleeker, 1849; Anguilla mowa Bleeker, 1852; Anguilla sidat Bleeker, 1852; Anguilla spengeli Weber, 1912. Status in the Arabian Peninsula. First report from the Arabian Peninsula by Attaala & Salim Rubaia (2005); confirmed by Freyhof et al . (2020:113). General distribution and Habitat. Indo-West Pacific: Seychelles, Mayotte (France), Madagascar and Mascarenes (La Réunion, Mauritius, Rodrigues) east to China and New Britain (Papua New Guinea), south to northern ... : Published as part of Esmaeili, Hamid Reza & Hamidan, Neshat, 2023, Inland fishes of the Arabian Peninsula: Review and a revised checklist, pp. 201-226 in Zootaxa 5330 (2) on page 206, DOI: 10.11646/zootaxa.5330.2.2, http://zenodo.org/record/8249316 ...